Pediatric emergency revisits of children with COVID-19. Issue 4 (19th May 2023) - Akcan Yildiz, Leman; Karaca Vural, Oznur; Tehci, Ali Kansu; Akca, Halise; Kurt, Funda; Akca Caglar, Ayla; Dibek Misirlioglu, Emine
ABSTRACT: Objective: This study was conducted to reveal the characteristics of pediatric emergency revisits of children with COVID-19 and the factors associated with clinical worsening and hospitalization at the revisit. Materials and Methods: In pediatric emergency visits of children between July 2020 and March 2021 with COVID-19, the patients who had a revisit within 7 days were included in the study. Demographic and clinical characteristics, test results, and the relationship of these variables with clinical worsening and hospitalization at the revisit were investigated. Results: In 6779 children with COVID-19, 284 (4.1%) patients included in the study. 51.8% of the patients were male, the median age was 11.1 years, and median time to revisit time was 2.0 days. The rates of clinical worsening and hospitalization were 9.1% and 14.7%, respectively. Children younger than 24 months and those with chronic diseases were more commonly hospitalized at the revisit. Though the frequency of laboratory and radiologic testing at the revisit was significantly increased compared to the first presentation, tests did not play an important role in the decision-making processes. More than 85% of patients were clinically mild at the first presentation and revisit. Conclusions: Children with a diagnosis of COVID-19 can revisit the emergency without evident clinical worsening. Since revisits cause increase in frequency of laboratory and radiological testing, preventing unnecessary revisits of children with COVID-19 can reduce the workload and cost of health care services. We may consider changing our perspective on revisit patients to make decisions based on clinical findings instead of obtaining for more laboratory tests.